Bank Attributes and Demographic Factors In Determining Customer Choice In Retail Banking: An Analytical Hierarchy Approach - Muhamad Jantan; Abdul Razak Kamaruddin; Ong Bian Hoe (Asian Academy of Management Journal, 1998)
Bank Attributes and Demographic Factors In Determining Customer Choice In Retail Banking: An Analytical Hierarchy Approach (PDF not available)